Vancomycin Area Under the Curve Dosing and Monitoring at an Academic Medical Center: Transition Strategies and Lessons Learned. (December 2020) - Gregory, Eric R.; Burgess, Donna R.; Cotner, Sarah E.; VanHoose, Jeremy D.; Flannery, Alexander H.; Gardner, Brian; Autry, Elizabeth B.; Forster, Derek W.; Burgess, David S.; Wallace, Katie L.
Due to the inconsistent correlation of vancomycin trough concentrations with 24-hour area under the curve (AUC) and a desire to reduce rates of vancomycin-associated acute kidney injury, an institutional guideline was implemented by the Antimicrobial Stewardship Team in September 2017 to monitor vancomycin using AUC. Three stages were utilized to organize the process: preparation, implementation, and evaluation. The preparation stage was used to present literature to key stakeholders, and pharmacy meetings focused on the development of a dosing and monitoring guideline. Along with institution-wide education, the implementation stage included information technology development and support. The evaluation stage was comprised of quality improvement and clinical research. Future plans include dissemination of the results and analyses. Numerous lessons were learned due to barriers experienced during the process, but the transition was successful.